1
$\begingroup$

For example the function $f(x)=\sqrt{x+2}-\sqrt{x}$ How do I find the limit as the function approaches infinity without graphing? Thanks a lot in advance!

$\endgroup$
3
10
$\begingroup$

$$\begin{array}{rcl} \sqrt{x+2}-\sqrt x &=& \dfrac{(\sqrt{x+2})^2 - (\sqrt x)^2}{\sqrt{x+2} + \sqrt x} \\ &=& \dfrac{2}{\underbrace{\sqrt{x+2}}_\infty+\underbrace{\sqrt x}_\infty} \\ &\to& 0 \end{array}$$

$\endgroup$
4
$\begingroup$

By the mean value theorem, $f(x+c)-f(x) =cf'(z) $ where $x \le z \le x+c$.

Therefore, if $f'(x) \to 0$ as $x \to \infty$, $f(x+c)-f(x) \to 0$ for any fixed $c$.

If $f(x) = \sqrt{x}$, $f'(x) =\dfrac1{2\sqrt{x}} \to 0 $ as $x \to \infty$. Therefore $\sqrt{x+c}-\sqrt{x} \to 0 $ as $c \to \infty$.

Note that the MVT gives the bounds $\dfrac{c}{2\sqrt{x}} \ge \sqrt{x+c}-\sqrt{x} \ge \dfrac{c}{2\sqrt{x+c}} $.

$\endgroup$
1
  • $\begingroup$ nice! though it uses calculus, this is really pretty. $\endgroup$
    – yberman
    Apr 18 '17 at 2:20
2
$\begingroup$

$$ f(x)=\sqrt{x+2} - \sqrt{x} = \sqrt{x} \left(\sqrt{x+2\over x} - 1 \right) = \sqrt{x} \left(\sqrt{1+{2\over x}} - 1 \right) $$ $$ =\sqrt{x} \left(1+{1\over x}+O\Big({1\over x^2}\Big) - 1 \right) ={1\over\sqrt{x}} + O\Big({1\over x^{3/2}}\Big) \ \to \ 0 \quad\mbox{ as }x\to\infty. $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.